EFFECT OF ORAL REHYDRATION SOLUTION ON HYDRATION STATE DURING 'SUMO' TRAINING. Issue 7 (11th March 2014) - Minami, K; Ishikawa, T; Ishida, J; Nakagawa, Y
Abstract : Background: Exercise in a hot environment can cause loss of water and electrolytes, which conveys tress on homeostasis. Objective: To maintain appropriate hydration status in such situation, it expects to be suitable for fluid replacement to drink oral rehydration solutions (ORS) which have higher sodium concentration and higher absorptive of water in the intestine than general purpose sports drinks (SPD). Design: Randomized crossover study. Setting: University SUMO League. Participants: 10 members of a university SUMO club voluntarily participated after providing written informed consent. Interventions: Participants ingested SPD or ORS with an equalized exercise load in a randomized crossover manner at a wet bulb globe temperature of 27–30°C. Main outcome measurements: Body weight, water distribution with bioelectrical impedance analysis, vital signs, blood analysis and visual analogue scale (VAS) for fatigue and thirst were evaluated between the two drinks. Values are expressed as mean±SD (SPD vs. ORS). Results: Differences were observed 15 min after training in the changes from the baseline of serum total protein (0.6±0.3 vs. 0.3±0.2 g/dL, P=.02), serum sodium (–1.4±2.1 vs. 0.2±2.0 mEq/L, P<.01), and VAS scores of fatigue (80±13 vs. 64±24, P=.03) and thirst (49±21 vs. 31±15, P=.03). Differences 75 min after training were also observed in the changes of extracellular fluid (0.3±0.2 vs. 0.5±0.2 L, P=.02), serum osmolarity (–2.7±4.0 vs. 0.4±3.5 mOsm, P=.03). Conclusions: The ORS rather than the SPD were shown to be more suitable to maintain hydration status in a hot environment of SUMO training. The intake of ORS should be considered upon exercise accompanied with marked perspiration.